Numerical study on the impact of wall structure on the thermal performance of double-channel porous solar wall - Qi, Xuejun; Lin, Shuang; Tao, Shuyan; Patchigolla, Kumar (Nature Research, 2022)
With the improvement of people’s living standards, they have higher requirements for indoor thermal comfort in the cold season. Solar wall utilizing solar energy for heating can reduce carbon emissions and achieve carbon neutrality. In the aspect of solar wall research, the influence of wall structure on the thermal performance of double-channel porous solar wall is limitedly investigated. In fact, the optimization design of wall structure is important for the thermal performance of solar wall and its applications. Therefore, a simplified three dimensional room model is built to study the influence of the wall structure on the thermal performance of porous solar wall by numerical simulation. With this model, different channel spacing and thickness of porous walls were used to determine the optimal design for a double-channel porous solar wall in terms of enhancing the heat storage. Moreover, the influence of the surface emissivity on the characteristics of heating and temperature field of double-channel porous solar wall are studied based on the optimal structure. The CFD simulation results indicate that the optimal structure parameters should include spacing of 0.08 m for channel 1, the porous wall thickness should be 0.08 m, and the air channel 2 spacing should be 0.06 m. The temperature of air channel 1 and air channel 2, the indoor temperature, and the heat storage of porous wall decrease with the increase of the surface emissivity of the porous wall. In order to improve the heat storage performance of double-channel porous solar wall, the outer surface of the porous wall should use a lower emissivity material. The outer surface emissivity of porous wall has a significant impact on the heat storage of the porous wall and little effect on the thermal storage wall. The temperature of porous wall is always higher than that of outdoor environment temperature.
Keywords: Energy storage; Renewable energy